Circular RNA Foxo3: A Promising Cancer-Associated Biomarker - Yang, Tianli; Li, Yang; Zhao, Feng; Zhou, Liuhua; Jia, Ruipeng (Frontiers in Genetics, 2021)
Circular RNAs (circRNAs) are a class of novel noncoding RNAs (ncRNAs). Emerging evidence demonstrates that circRNAs play crucial roles in many biological processes by regulating linear RNA transcription, downstream gene expression and protein or peptide translation. Meanwhile, recent studies have suggested that circRNAs have the potential to be oncogenic or anti-oncogenic and play vital regulatory roles in the initiation and progression of tumors. Circular RNA Forkhead box O3 (circ-Foxo3, hsa_circ_0006404) is one of the most studied circular RNAs. Previous studies have reported that circ-Foxo3 is involved in the development and tumorigenesis of a variety of cancers (bladder, gastric, acute lymphocytic leukemia, glioma, etc.). In this review, we summarize the current studies concerning circ-Foxo3 deregulation and the correlative mechanism in various human cancers. We also point out the potential clinical applications of this circRNA as a biomarker for cancer diagnosis and prognosis.